A new species of Artimpaza Thomson (Coleoptera, Cerambycidae, Cerambycinae) from China, with a key to the Chinese species of the genus - Tian, Lichao; Chen, Li; Li, Zhu (Zootaxa, 2012)
A new species, Artimpaza brevilineata Tian & Chen, sp. nov. (Coleoptera: Cerambycidae: Cerambycinae), is described from China, and a key to the Chinese species of Artimpaza Thomson is provided.